Transforming community health services for children and young people who are ill: a quasi-experimental evaluation - Gemma Spiers; Victoria Allgar; Gerry Richardson; Kate Thurland; Sebastian Hinde; Yvonne Birks; Kate Gridley; Helen Duncan; Susan Clarke; Linda Cusworth; Gillian Parker (National Institute for Health Research, 2016)
Background: Children's community nursing (CCN) services support children with acute, chronic, complex and end-of-life care needs in the community. Objectives: This research examined the impact of introducing and expanding CCN services on quality, acute care and costs. Methods: A longitudinal, mixed-methods, case study design in three parts. The case studies were in five localities introducing or expanding services. Part 1: an interrupted time series (ITS) analysis of Hospital Episode Statistics on acute hospital admission for common childhood illness, and bed-days and length of stay for all conditions, including a subset for complex conditions. The ITS used between 60 and 84 time points (monthly data) depending on the case site. Part 2: a cost-consequence analysis using activity data from CCN services and resource-use data from a subset of families (n = 32). Part 3: in-depth interviews with 31 parents of children with complex conditions using services in the case sites and a process evaluation of service change with 41 NHS commissioners, managers and practitioners, using longitudinal in-depth interviews, focus groups and documentary data. Findings: Part 1: the ITS analysis showed a mixed pattern of impact on acute activity, with the greatest reductions in areas that had rates above the national average before CCN services were introduced and significant reductions in some teams in acute activity for children with complex conditions. Some models of CCN appear to have more potential for impact than others. Part 2: the cost-consequence analysis covered only part of the CCN teams' activity. It showed some potential savings from reduced admissions and bed-days, but none that was greater than the total cost of the services. Part 3: three localities implemented services as planned, one achieved partial service change and one was not able to achieve any service change. Organisational stability, finance, medical stakeholder support, competition, integration with primary care and visibility influenced the planning and implementation of new and expanded CCN services. Feeling supported to manage their ill child at home was a key outcome of using services for parents. Various service features contributed to this and were important in different ways at different times. Other outcomes included being able to avoid hospital care, enabling the child to stay in school, and getting respite. Although parents judged that care was of high quality when teams enabled them to feel supported, reassured and secure in managing their ill child at home, this did not depend on a constant level of contact from teams. Limitations: Delays in service reconfigurations required adaptation of research activity across sites. Use of administrative data, such as Hospital Episode Statistics, for research purposes is technically difficult and imposed some limitations on both the ITS and the cost-consequence analyses. Conclusions: Large, generic CCN teams that integrate acute admission avoidance for all children with support for children with complex conditions and highly targeted teams for children with complex conditions offer the possibility of supporting children more appropriately at home while also making some difference to acute activity. This possibility remains to be tested further. Future work: Further work should refine the evidence on outcomes of services by looking at outcomes in promising models, value for money and measuring quality-based outcomes. Funding: The National Institute for Health Research Health Services and Delivery Research Programme.